How To Develop Dalam Fungsi Dan Manfaat Media Pembelajaran Di Sekolah Dasar - Futri Zaharah; Miftahul Husna; Nadia Sa’bani; Siti Aminah; Wismanto Wismanto (Universitas Maritim AMNI Semarang, 2024)
Quality in learning greatly affects the level of student success in learning. In improving quality, of course, there must be application in learning, namely by developing functions and benefits in learning media in elementary schools. Media is a teaching tool that presents several messages and information about facts, concepts, procedures, and principles that are under the subject matter. This research uses qualitative methods with descriptive research types. The purpose of this study is to provide an overview and details of field data collected in developing the functions and benefits of the latest learning media at the elementary level. Data collection techniques using literature studies. This research was conducted through several stages, namely: 1) determining the research subject, 2) studying the research topic, 3) collecting research information, and 4) analyzing data. The results of the study are by conveying messages or information in the teaching-learning process which aims to develop learning motivation and attention to students' interest in lessons. As well as in learning media that contain subject matter used by educators in the learning process, and have two components that are very important for learning success, it can be decided that learning media exist in various types and forms, ranging from the easiest to the most sophisticated. Therefore, the choice of learning media must be tailored to learning objectives, student demographics, availability, technical quality, cost, flexibility, user capabilities, and available time. To improve a quality generation in the future, it is necessary to develop the functions and benefits of learning media in the teaching and learning process, especially in elementary schools.